Application of A Communicative Approach in Learning Speaking Skills in Class XI Students of SMA Jaya Negara Makassar - Rosary Iriany; Nuzul Tenriana; Andi Muhdar (Universitas Muhammadiyah Enrekang, 2023)
This research aims to determine speaking skills by applying a communicative approach to class XI students at SMA Jaya Negara Makassar. This research is experimental research that uses a comparison between two groups, namely the experimental group and the control groupThe results of this research indicate that the learning outcomes in learning speaking skills for class Among the 21 experimental class students, there were 19 students who scored>75. In contrast to the learning outcomes in control class learning, it is categorized as inadequate because the scores obtained by students have not reached the set criteria, namely 85% of the total number of students who obtained scores <75. Meanwhile, the students' score only reached 4.8% or 1 person. Thus, it can be said that the learning outcomes in teaching speaking skills for class XI students at SMA Jaya Negara Makassar by applying a communicative approach are very effective.